Mormon student religiosity and higher education - Marshall, Craig Lithgow (1996)
This study examines the religiosity of Mormon college students in Britain and its relationship with higher education and their church. Past research has demonstrated a negative association between the level and length of education and religiosity. However, many American studies identify in Mormon students an exception to this general trend. The initial hypothesis to be tested is that British Mormons will show the same resistance to the secularizing influence of higher education as their American counterparts, despite an apparently less favourable social environment. A further proposal is that various agencies of Church support, particularly the Institutes of Religion, are an important element in sustaining religious commitment. Research methods include questionnaire surveys of students, Church administrators and Institute instructors. Religiosity scales are developed from the student questionnaire through factor analysis, utilizing procedures developed in America. Differences between the British and American scales underline the complex nature of religiosity and reflect the generally contradictory and inconclusive character of wider research in this field. The scales are used to measure student religiosity and correlations with other variables are calculated. Results confirm that for Mormon students in Britain there is no significant association between years of higher education and religiosity. Associations are demonstrated between religiosity and various Church agencies, including Institute, thus supporting the second hypothesis; however the dependency in several relationships is problematic and the influence of these agencies is not conclusive. This result stimulated a consideration of other areas of belief and practice likely to be important; characteristics of LDS faith are identified which may be significant for the resilience of Mormon religiosity.